Pembuatan Media Pembelajaran Berbasis Artificial Intelligence untuk Meningkatkan Kompetensi Guru Bahasa Indonesia SMA di Kabupaten Batu Bara - Mardinal Tarigan; Parulian Sibuea; Siti Mauliddina; Nurul Ilmi (SAWERIGADING, 2025)
This community service initiative is the result of a study conducted to enhance the competencies of Indonesian language teachers in Batubara Regency through training in the development of teaching media based on artificial intelligence (AI). The training employed a Participatory Action Research (PAR) approach, which emphasizes community empowerment. The implementation stages consisted of: (1) planning, (2) implementation, and (3) evaluation. The collection of primary data and information was carried out by the baseline survey method and Indonesian teachers in Batu Bara in participatory media production (PAR). The foundational survey was carried out through interviews with Indonesian language teachers and direct field observations. Meanwhile, the implementation of PAR is taken in accordance with the specifications of the rules and principles, which involve the aspiration of participation (participation) of Indonesian teachers. The training was carried out for 3 days with training on Artificial Intelligence (AI) tools, namely POP AI, Magicshool, Educaplai AI, Prezzi AI, Perplexity, Quillbot, and Open Knowledge Maps. The results of the implementation show that there is an increase in teachers' competence to understand, use, and integrate AI tools in learning. The obstacles to the implementation of AI are internet connection facilities and paid premium tools accounts.  AbstrakPengabdian ini merupakan hasil kajian yang dilakukan untuk meningkatkan kompetensi guru Bahasa Indonesia di Kabupaten Batubara melalui pelatihan pembuatan media ajar berbasis artificial intelligence (AI). Pendekatan yang digunakan dalam pelatihan ini adalah pendekatan Participatory Action Research (PAR) yang berorientasi pada pemberdayaan masyarakat. Tahapan pelaksanaan terdiri atas (1) perencanaan, (2) pelaksanaan, dan (3) evaluasi. Pengumpulan data dan informasi primer dilakukan dengan metode survei pendasaran (baseline survey) dan guru Bahasa Indonesia di Batubara dalam pembuatan media secara partisipatif (participatory action research/PAR). Survei pendasaran dilaksanakan melalui wawancara terhadap guru Bahasa Indonesia serta pengamatan lapangan langsung (direct observation). Sementara itu pelaksanaan PAR ditempuh sesuai dengan spesifikasi kaidah dan prinsipnya, yakni melibatkan aspirasi peran serta (partisipasi) guru Bahasa Indonesia. Pelatihan dilaksanakan selama 3 hari dengan pelatihan tools Artificial Intelligence (AI) yakni POP AI, Magicshool, Educaplai AI, Prezzi AI, Perplexity, Quillbot dan Open Knowledge Maps. Hasil pelaksanaan menunjukkan bahwa adanya peningkatan kompetensi guru memahami, menggunakan dan mengintegrasikan tool AI dalam pembelajaran. Adapun kendala pada implementasi penerapan AI ialah fasilitas koneksi internet dan akun premium tools yang berbayar.